Using Resource Consumption Accounting and Material Flow Cost Accounting to Achieve Product Sustainability in Iraqi Economic Units (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to identify the cognitive aspects of the research variables and the importance of applying resource consumption accounting and material flow cost accounting in Iraqi economic units, and its role in achieving product sustainability by identifying losses and idle energy during the production process, as the research problem represents that the company is exposed to many challenges and pressures in achieving a balance between the optimal use of resources and maintaining competitiveness and achieving sustainability for its products. To address this problem, the researcher used the application of the resource consumption accounting system and material flow cost accounting technology to achieve product sustainability by tracking the stages that the product goes through during the production process from the stage of purchasing raw materials to the post-use stages and identifying losses and unused energy. The researcher conducted field work in the National Company for Chemical and Plastic Industries and reached a set of conclusions, the most important of which is that using resource consumption accounting and material flow cost accounting helps to identify losses during the production process and unused energy for the pallet product. As for the most important recommendations, he recommended the necessity of using and adopting the company's management of the resource consumption accounting system and material flow cost accounting technology because provides detailed information.